Alternate Thermomechanical Heat Treatment Cycles for the Enhancement in Hardness and Tensile Properties of Commercial Grade AA6061 - Ramakrishna Vikas Sadanand; Sathyashankara Sharma; P. R. Prabhu (Materials Research, 2022)
Abstract Numerous research incorporating precipitation hardening and/or strain hardening on Al-Mg-Si alloys has demonstrated improved mechanical properties in the alloys. However, there is a lack of research on how these processes can be combined efficiently to provide better strength and hardness for the alloys. The present study describes the effects of low temperature thermomechanical treatment (LTMT - combination of conventional age hardening and strain/work hardening) carried at two isothermal aging temperatures on the hardness and strength of the aluminium alloy 6061 (AA6061). Further, an innovative LTMT process is also proposed, which aims at further enhancing the mechanical properties of the alloy. The study revealed the increase in degree of deformation improved the strength and hardness of the alloy with reduced aging time. The effect of the degree of deformation, pre-deformation, and alternate deformation and aging cycles on the hardness and strength of the alloy was studied with the help of fracture surface analysis.